Examining the Effect of Job Design on Staff Satisfaction and Productivity. A Case Study of MTN Uganda Head Office Kampala - Josephine Ater Abiting (Uganda Christian University, 2024)
This study examines the effects of job design on staff satisfaction and productivity at MTN Uganda. The research explores the implementation of job structuring, flexi-time, and flexible work arrangements as part of job design approaches to improve employee satisfaction and performance. Data were collected using questionnaires distributed to a sample of 289 employees across various departments. The findings reveal a positive correlation between well-structured job design and higher levels of employee satisfaction and productivity. The study recommends further refinement of flexible work arrangements to meet evolving employee needs.
Undergraduate research